Supporting digital competency development for vocational education student teachers in distance education - Deschênes, Michelle; Dionne, Lucie; Parent, Séverine (Frontiers in Education, 2024)
In Quebec, aspiring vocational education teachers must enroll in a bachelor’s degree program in vocational education. At the Université du Québec à Rimouski, the Bachelor of Vocational Education (BVE) program is offered remotely and asynchronously in a digital learning environment. This project explores what digital competency resources are available to BVE students and the characteristics of the resources that students know, use and deem satisfactory. This quantitative descriptive study was carried out in two phases. In the first phases, interviews and a literature search were used to identify the resources, which we analyzed according to the Analytical Framework of Resources Supporting Digital Competency Development (De Clercq et al., 2022) and the Digital Competency Framework (Ministère de l’Éducation et de l’Enseignement supérieur, 2019). In the second phase, 137 students evaluated 36 identified resources through a questionnaire. The findings reveal that the resources are not widely known, and even when known, they are infrequently used. However, when used, they are generally deemed satisfactory. Notably, resources are more frequently used when required for assessment in the introductory BVE course. Additionally, workshops are rated more satisfactory than videos. The results underscore the need for program instructors to actively promote these resources and suggest that further research is needed to better understand student needs.